Traumatic dental injuries in young children - Takahashi, Karine; Faria, Isabela Copetti; Neves, Natália Oliveira; Montano, Sthepane Barbosa; Araujo, Heitor Ceolin (ARCHIVES OF HEALTH INVESTIGATION, 2019)
Introduction: Dental trauma is a frequent occurance in Dentistry. They often occur in early childhood, between 0 to 3 years old, when children begin to learn their first steps, to play and run, because their habilities are not refined. Objective: The purpose of this article is to verify the occurance of traumatic dental injury in primary teeth in a children population. Material and Method: seventy-eight child from 0 to 6 years old male and female were evaluated. The study was conducted in Regional Hospital of Presidente Prudente. Children were evaluated by a questionary about occurance of traumatic injury, cause and search for attendance. The data were collected and submited to Spearman correlation test. Results: Traumatic dental injury occurs in deciduous teeth in (44,8%) of the population, more common in males (68,5%), at two years old (28,5%) and in front superior region (91,5%) in the upper central incisors (48,5%). Conclusion: By the use of correlation test of Spearman, it was possible to verify that there is a positive correlation between the factors: darkness and mobility, darkness and search for treatment, early loss and satisfactory treatment and search for treatment and satisfactory treatment. Descriptors: Tooth Injuries; Dentition; Dental Care. Referências Assunção LRS, Cunha RF, Ferelle A. Análise dos traumatismos e suas seqüelas na dentição decídua: uma revisão de literatura. Pesqui bras odontopediatria clín integr. B. Odontopediatria. Clin. Integr. 2007;7(2):173-79. Duarte DA, Bonecker MJS, Sant’anna GR, Suga SS. Caderno de odontopediatria: lesões traumáticas em dentes decíduos: tratamento e controle. Santos; 2001. Moss SJ, Macaro H. Examination, evaluation and behavior management following injury to primary incisors. NY State Dent J. 1985;51(2):87-92. Campos JADB, Zuanon ACC, Pansani CA. Traumatismo na dentição decídua e suas conseqüências na dentição permanente. ROBRAC 2001;10(30):26-8. Alexandre GC, Campos V, Oliveira M. Luxação intrusiva de dentes decíduos. Rev Assoc Paul Cirur Dent. 2000;54(3):215-19. Santos V, Seabra S, Chevitarese Z. Traumatismo dentário numa visão de promoção de saúde. Saúde & Amb Rev. 2010;5(1):1-7. Zembruski C. Estudo da prevalência de traumatismos na dentição decídua em pré- escolares do município de Canoas RS [dissertação]. Campinas: Universidade Camilo Castelo Branco; 2001. Cunha RF, Pugliese DMC, Vieira AE. Oral trauma in Brazilian patients aged 0-3 years. Dent traumatol. 2001;17(5):210-12. Della Valle D, Chevitarese ABA, Modesto A, Castro LA de. Frequência de traumatismo dentário em bebês. Rev Ibero-am Odontopediatr Odontol Bebê. 2003;6(34):464-69. Meira R, Barcelos R, Primo LG. Respostas do complexo dentino-pulpar aos traumatismos em dentes decíduos. JBP – J Bras Odontopediatr Odontol Bebê. 2003;6(29):50-5. Porto RB, Freitas JS, Cruz MR, Bressani AE, Barata JS, Araújo FB. Prevalence of dento-alveolar traumatisms in the urgency pediatric dental clinic of FO UFRGS. Rev Fac Odontol Porto Alegre. 2003;44(1):52-6. Vasconcellos RJH, Oliveira DM, Nogueira RVB, Maciel AP, Cordeiro MC. Trauma na dentição decídua: enfoque atual. Rev cir traumatol buco-maxilo-fac. 2003;3(2):17-24. Simões FG, Leonardi DP, Baratto Filho F, Ferreira EL, Fariniuk LF, Sayão SMA. Fatores etiológicos relacionados ao traumatismo alvéolo-dentário de pacientes atendidos no pronto socorro odontológico do Hospital Universitário Cajuru. RSBO. 2004;1(1):50-5. Scarpari CEO, Possobon RF, Moraes ABA. Ocorrência de traumatismo em dentes decíduos de crianças atendidas no Cepae-FOP/UNICAMP. J Bras Odontopediatr Odontol Bebê. 2004;7(35):33-40. Zaze ASF, Assunção LRS, Provenzano MGA, Franzin LCS, Ferelle A, Cunha RF. Avaliação de traumatismos dentários em crianças assistidas em um pronto atendimento odontológico. Pesq Odontol Bras. 2004;18(sup):221. Oliveira FAM, Oliveira MG, Orso VA, Oliveira VR. Traumatismo Dentoalveolar: revisão de Literatura, Rev cir traumatol buco-maxilo-fac. 2004;4(1):15-21. Amorim NA, Silva TRC, Santos LM, Tenório MDH, Reis JIL. Urgência em Odontopediatria: perfil de atendimento da Clínica Integrada Infantil da FOUFAL. Pesq Bras Odontoped Clin Integr. 2007;7(3):223-27. Moura LFAD, Ferreira DLA, Melo CP, Sady MCLM, Moura MS, Mendes RF et al. Prevalência de injúrias traumáticas em crianças assistidas na clínica odontológica infantil da Universidade Federal do Piauí, Brasil. Pesq. Bras. Odontopediatria Clin Integr. 2008;8(3):341-45. Gulinelli JL, Saito CT, Garcia-Júnior IR, Panzarini SR, Poi WR, Sonoda CK et al. Occurrence of tooth injuries in patients treated in hospital environment in the region of Araçatuba, Brazil during a 6-year period, Dent Traumatol. 2008;24(6):640-44. Tzigkounakis V, Merglová V. Attitude of Pilsen primary school teachers in dental traumas. Dent Traumatol. 2008;24(5):528-31. Trombini CS, Feldens EG, Feldens CA. Luxação intrusiva em dentes decíduos: relato de caso, Stomatos, 2008;14(27):74-86. Cabral ACR, Duarte DA, Climene Valentim. Prevalência das injúrias traumáticas na dentição decídua. Rev odontol Univ Cid São Paulo. 2009;21(2):137-43. Oliveira MSB, Carneiro MC, Amorim TM, Maia VN, Alvarez AV, Vianna MIP et al. Contexto familiar, traumatismo dentário e oclusopatias em crianças em idade pré-escolar: ocorrência e fatores associados. Rev Odontol UNESP. 2010;39(2):81-8. Cardoso M, de Carvalho Rocha MJ. Traumatized primary teeth in children assisted at the Federal University of Santa Catarina, Brazil. Dent Traumatol. 2002;18(3):129-33. Siqueira MB, Gomes MC, Oliveira AC, Martins CC, Granville-Garcia AF, Paiva SM. Predisposing factors for traumatic dental injury in primary teeth and seeking of post-trauma care. Braz Dent J. 2013;24(6):647-54. Firmino RT, Siqueira MBLD, Vieira-Andrade RG, Gomes GB, Martins CC, Paiva SM et al. Prediction factors for failure to seek treatment following traumatic dental injuries to primary teeth. Braz oral res. 2014;28(1):1-7. Losso EM, Tavares MCR, Bertoli FMP, Baratto Filho F. Tarumatismo dentoalveolar na dentição decídua. RSBO. 2011;8(1):e1-20. Chowdary GN, Hemalatha R, Vijayakumar R, Ganhesh R, Selvakuma H, Mangauyarkarasi S. Prevalence of traumatic dental injuries in primary teth: A retrospective study. SRM J Res Dent Sci. 2014;5(1):11-3 Souza Filho MD, Moura MS, Araújo RSRM, Araújo MAM, Moura LFAD. Prevalência de traumatismo dentário em pré-escolares de Teresina, PI. Arq Odontol. 2011;47(1):18-24. Granville-Garcia AF, Menezes VA, Lira PIC. Prevalência e fatores sócios-demográficos associados ao traumatismo dentário em pré-escolares. Odontol clín-cient. 2006;5(1):57-64. Kawabata CM, Sant'Anna GR, Duarte DA, Mathias MF. Estudo de injúrias traumáticas em crianças na faixa etária de 1 a 3 anos no município de Barueri, São Paulo, Brasil. Pesqui Bras Odontopediatria Clin Integr. 2007;7(3):229-33. Sousa DL, Moreira Neto JJS, Gondim JO, Bezerra Filho JG. Prevalência de trauma dental em crianças atendidas na Universidade Federal do Ceará / Prevalence of dental trauma in children attending the Federal University of Ceará. Rev Odonto Ciênc. 2008;23(4):355-59. Rajab LD. Traumatic dental injuries in children presenting for treatment at the Department of Pediatric Dentistry, Faculty of Dentistry, Universit of Jordan. Dent Traumatol. 2003;19(1):6-11. Kramer PF, Gomes CS, Ferreira SH, Feldens CA, Viana ES. Traumatismo na Dentição Decídua e Fatores Associados em Pré-Escolares do Município de Canela/RS, Pesq Bras Odontoped Clin Integr. 2009;9(1):95-100. Wendt FP, Torriani DD, Assunção MC, Romano AR, Bonow ML, da Costa CT, Goettems ML et al. Traumatic dental injuries in primary dentition: epidemiological study among preschool children in South Brazil. Dent Traumatol.2010;26(2):168-73. Bhayya DP, Shyagali TR. Traumatic injuries in the primary teeth of 4- to 6-year-old school children in gulbarga city, India: a prevalence study. Oral Health Dent Manag. 2013;12(1):17-23. Al-Majed I, Murray JJ, Maguire A. The Prevalence of dental trauma in 5-6 and 12-14 year-old boys in Riyadh, Saudi Arabia. Dent Traumatol. 2001;17(4):153-58. Chalissery VP, Marwah N, Jafer M, Chalisserry EP, Bhatt T, Anil S. Prevalence of anterior dental trauma and its associated factors among children aged 3-5 years in Jaipur City, India – A cross sectional study. J Int Soc Prev Community Dent. 2016;6(1):35-40. Hanan SA, Costa SK. Conhecimento dos professores de 1ª a 4ª série de escolas públicas municipais de Manaus/AM frente à avulsão dentária. Pesq Bras Odontoped Clin Integr 2010;10(1):27-33. Glendor U. Epidemiology of traumatic dental injuries-12 year review of the literature. Dent Traumatol. 2008;24(6):603-11. Khahabuka FK, Plasschaert A, van 't Hof M. Prevalence of teeth with untreated dental trauma among nursery and primary school pupils in Dae es Salaam, Tanzania. Dent Traumatol. 2001;17(3):109-13.